Penentuan Rute Distribusi Gas LPG 3 kg Dengan Menggunakan Metode Saving Matrix (Studi PT Carolinee Putri Anwar Lubuklinggau) - Wijaya, Odi (Management Insight: Jurnal Ilmiah Manajemen, 2024)
This study aims to determine the optimal distribution route and minimum distribution costs for PT Caroline Putri Anwar Lubuk linggau using the saving matrix approach. This study uses qualitative research. Data collection was used through interviews and observations at the research location by conducting interviews with key informants and requesting documents for shipping 3 KG of LPG gas from the company. Data processing is used using the saving matrix method with the nearest neighbor determine determining the order of visits to the base with the help of analysis tools. The results of this study note that in one day there are 6 routes and the distance that must be traveled is 2,856.6 KM in one month with a distribution fee of Rp.41,508,938.5 in one month, so the company can reduce the distance traveled by 33.2% or 1,423.4 km and can save distribution costs up to 3.8% or Rp. 1,648,736.5 in one month using three units of trucks with a truck capacity of 560 units of LPG Gas. Keywords: Distribution, Transportasi, Saving Matrix